Analysis of Language Error at Morphological Level on Covesia.com Online News Portal - Harefa, Destin Talenta; Anggraini, Meilani; Rasyid, Yulianti (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This study took three samples of article titles: Talempong Batu and the Mystery of the Lost Tuanku Nan in Limapuluh Kota District, April 19, 2022 edition, West Sumatra Consultants Association, Strengthening Alignment with the Use of Regional Products, May 21, 2022 edition, and the Padang Adityawarman Museum Exhibits Gold and Silver Jewelry from Minangkabau and Yogyakarta, 28 October 2022 edition. This study aims to analyze the appropriate use of language. The stages used in data collection in this study are, first, data collection from data sources by reading and recording. Both data analysis and correction efforts. The final stage is drawing conclusions. The technique used by the author in analyzing the data is by reading and writing techniques, meaning that every data obtained is read carefully then written errors in the language of morphology in the field of morphology and corrections are also written. The method used in this research is descriptive qualitative research. The results of this study are the analysis of language errors at the morphological level including: (a) errors in using affixation, (b) writing standard words, (c) affixation that does not melt, (d) compound words, (e) reduplication process.